2010
DOI: 10.1177/1934578x1000500427
|View full text |Cite
|
Sign up to set email alerts
|

Nepetalactone Content and Antibacterial Activity of the Essential Oils from Different Parts of Nepeta persica

Abstract: The essential oils from the flower, leaf, stem and root of Nepeta persica Boiss., analyzed by GC and GC/MS, were shown to contain 4aβ,7α,7aβ-nepetalactone (58.5%, 62.3%, 66.2% and 27.1%, respectively), and 4aα,7α,7aβ-nepetalactone (33.0%, 28.3%, 24.9% and 7.6%, respectively). The other main component of the flower and stem oils was α-pinene (3.6% and 4.4%) and of the leaf oil β-ocimene (3.6%). In the root oil, other main constituents were α-pinene (40.4%), α-amorphene (5.3%), γcadinene (2.9%), and cis-calamene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Several of these volatile compounds, such as DMDS, methyl ketone and toluene, have been previously detected in the headspace of cultures of many strains of Pseudomonas spp and from B. cepacia cultured in trypticase soy 22 . Although diverse volatile compounds, for example, DMDS, are able to inhibit spore germination in other fungi, such as Paecilomyces lilacinus , Pochania chlamydospora and Chlonostachys rosea , 23 in this work we found novel compounds, including α-pinene, ocimene, limonene and fencona, which are typically associated with plants and fruits with antibacterial properties, 24 suggesting that they play an important role in the antagonistic antifungal mechanism associated with this bacterium.…”
Section: Resultsmentioning
confidence: 64%
“…Several of these volatile compounds, such as DMDS, methyl ketone and toluene, have been previously detected in the headspace of cultures of many strains of Pseudomonas spp and from B. cepacia cultured in trypticase soy 22 . Although diverse volatile compounds, for example, DMDS, are able to inhibit spore germination in other fungi, such as Paecilomyces lilacinus , Pochania chlamydospora and Chlonostachys rosea , 23 in this work we found novel compounds, including α-pinene, ocimene, limonene and fencona, which are typically associated with plants and fruits with antibacterial properties, 24 suggesting that they play an important role in the antagonistic antifungal mechanism associated with this bacterium.…”
Section: Resultsmentioning
confidence: 64%
“…The various species of genus Nepeta have been known to have a wide range of medicinal properties viz. anti‐spasmodic, anti‐tussive, diuretic, febrifuge, anti‐asthmatic, emmenagogue, diaphoretic, and sedative effects (Formisano, Rigano, & Senatore, ; Kumar, Mathela, Tewari, & Singh, ; Shafaghat and Oji, ). Further, many species of this genus have also been reported to use against the treatment of cardiac thrombosis, angina pectoris, liver, kidney, stomach, and tooth ailments (Formisano et al, ; Sharma and Cannoo, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to review, N. nuda possesses antimicrobial (Alim et al, 2009;Gormez et al, 2013;Smiljković et al, 2018;Ðordević et al, 2019) and virocidal activity (Angelova et al, 2016;Todorov et al, 2015), as well as antioxidant (Alim et al, 2009;Aras et al, 2016b;a;Cvetković et al, n.d.;Sarikurkcu et al, 2018;2019;Ðordević et al, 2019), anticancer (Kabalay et al, 2018), and allelopathic (Bozari et al, 2013;Bozok et al, 2017;Dragoeva et al, 2017) properties. It has been reported that nepetalactones have antibacterial, antifungal, insecticidal and antioxidant activities (Adiguzel et al, 2009;Grbic-Ljaljevic et al, 2008;Reichert et al, 2019;Shafaghat and Oji, 2010;Zhu et al, 2012). Apart from these activities, their enjoyable flavor and scent is an additional benefit.…”
Section: Pharmacologymentioning
confidence: 99%